Rancang Bangun Sistem Informasi Pendaftaran Pasien Berbasis Website di Rumah Sakit Permata - Ekadianti, Ririn Yulia; Voutama, Apriade; Ridha, Azhari Ali (Universitas Indraprasta PGRI Jakarta, 2024)
Permata Hospital currently relies on a manual record-keeping system for patient registration, which is inefficient. The purpose of this research is to enhance the accuracy and efficiency of the patient registration process at Permata Hospital by designing a web-based patient registration information system. The research methodology employed in this study is the waterfall method, beginning with system requirements analysis, system design, implementation, testing, and maintenance. The expected outcome of this research is the development of a system that can process patient registrations effectively and efficiently. With the implementation of this information system, that it will reduce registration queues at the counters and facilitate patients in the registration process. Additionally, this system will assist hospital administrative staff in document archiving and patient registration data management.